RISIKO KREDIT DAN PROFITABILITAS: PERAN STRUKTUR MODAL SEBAGAI VARIABEL MODERASI - Nindytia Puspitasari Dalimunthe; Mutiasari Nur Wulan; Nurul Husna (Universitas Teknokrat Indonesia, 2023)
This study examines the effect of credit risk towards profitability. And also, to examine whether the capital structure lower or strengthen the effect of credit risk towards profitability. This study implements quantitative analysis in order to examine the effect of credit risk towards profitability with capital structure as moderating variable. Data obtained from annual report of banking subsector from year 2010-2020. NPL, DER, and ROA used as proxies for credit risk, capital structure, and profitability. The result shows that credit risk has negative effect on profitability. It shows that higher credit risk could affect lower profitability of the banks. When Capital structure sets as moderating variable, it shows no effect on profitability. This study only examines the effect of credit risk towards profitability. Future research could use other variables to determine what variable that contributes to profitability bank should evaluate credit policy by considering the NPL ratio because higher NPL will bring to lower profitability